Clinical characteristics of IgA nephropathy associated with low complement 4 levels. (24th December 2014) - Zhu, Bin; Zhu, Cai-Feng; Lin, Yi; Perkovic, Vlado; Li, Xian-Fa; Yang, Ru; Tang, Xuan-Li; Zhu, Xiao-Ling; Cheng, Xiao-Xia; Li, Qiang; Chen, Hong-Yu; Sun, Yue; et al.
Abstract: Objective : C4 deficiency is the most commonly inherited immune disorder in human. The present study investigated the characteristics of the IgAN patients with low serum C4 levels. Methods : We performed a prospective observational study. Clinical as well as histopathologic parameters were assessed. A Kaplan–Meier survival analysis was performed concerning the primary outcome defined as the serum creatinine increased 1.5-fold from baseline. The prognostic significances of clinical and histopathologic parameters were determined using Cox proportional hazards models. Results : Five-hundred twelve biopsy proven IgAN cases were available for analysis with a median follow-up of 38.4 months. Ninety-nine cases (19.34%) presented with low C4 levels (LowC4 group) and the other 413 cases did not (NlowC4 group). At the time of renal biopsy, renal injury was lighter in the LowC4 group compared with the NlowC4 group. Renal C4 deposition was significantly decreased while IgM deposition was increased in the LowC4 group. A correlation analysis shows that lower C4 levels were associated with better renal presentations at biopsy. However, the risk of developing the primary outcome was significantly greater in those with low C4 levels. Specifically, during the follow-up period, the risk of developing primary outcome was nearly ten folds higher in those with low C4, compared to those without low C4. Conclusion : There is a high prevalence of low C4 levels in IgAN patients. These patients with low C4 levels exhibited better renal presentations at the time of renal biopsy, whereas might be associated with a poor prognosis.